Mental health lived experience academics in tertiary education: The views of nurse academics - Happell, B.; Wynaden, Dianne; Tohotoa, Jenny; Platania-Phung, C.; Byrne, L.; Martin, G.; Harris, S. (2015)
© 2013 Elsevier Ltd. Background: Australian national mental health strategy emphasises inclusion of people diagnosed with mental illness in all areas of mental health care, policy development and education of health professionals. However, the way this inclusion has translated to Australian universities is relatively unexplored. Objectives: Explore views of nurse academics regarding service user involvement in nursing education programmes. Design: Qualitative exploratory. Settings: Australian universities offering educational programmes in nursing at postgraduate and undergraduate levels. Participants: Thirty four participants from 27 Australian universities participated. Methods: Data were collected using semi-structured telephone interviews with academics involved in teaching and/or coordinating undergraduate and/or postgraduate mental health nursing contents. Data were analysed using content analysis based on four cognitive processes: comprehending, synthesising, theorising and re-contextualising data. Results: Four major themes emerged: good idea? long way to go; conceptualising the service user academic role; strengths of lived experience led student learning; and barriers to implementation. Conclusions: Findings indicated strong support for including mental health service users in teaching nursing students. However, at most universities service user engagement was often an informal arrangement, lacking clear guidelines and limited by financial barriers and the positioning of mental health nursing within curricula.